TANGO ‐ a screening tool to identify comorbidities on the causal pathway of nocturia. (12th February 2017) - Bower, Wendy F.; Rose, Georgie E.; Ervin, Claire F.; Goldin, Jeremy; Whishaw, David M.; Khan, Fary
Abstract : Objectives: To develop a robust screening metric for use in identifying non‐lower urinary tract comorbidities pertinent to the multidisciplinary assessment of patients with nocturia. Methods: Variables having a significant risk association with nocturia of greater than once per night were identified. Discriminating items from validated and reliable tools measuring these comorbidities were identified. A self‐completed 57‐item questionnaire was developed and a medical checklist and pertinent clinical measures added. Pre‐determined criteria were applied to retain or remove items in the development of the Short‐Form (SF) screening tool. The tool was administered to 252 individuals with nocturia who were attending either a tertiary level Sleep, Continence, Falls or Rehabilitation service for routine care. Data collected were subjected to descriptive analysis; criteria were applied to reduce the number of items. Using pre‐determined domains, a nocturia screening metric, entitled TANGO, was generated. The acronym TANGO stands for Targeting the individual's Aetiology of Nocturia to Guide Outcomes . Results: The demographic characteristics of the sample are described, along with item endorsement levels. The statistical and structural framework to justify deleting or retaining of items from the TANGO Long‐Form to the SF is presented. The resultant TANGO‐SF patient‐completed nocturia screening tool is reported. Conclusions: A novel all‐cause diagnostic metric for identifying co‐existing morbidities of clinical relevance to nocturia in patients who present across disciplines and medical specialties has been developed. TANGO has the potential to improve practice and smooth inequalities associated with a siloed approach to assessment and subsequent care of patients with nocturia.